2009
DOI: 10.1063/1.3077124
|View full text |Cite
|
Sign up to set email alerts
|

Stacking-fault structure explains unusual elasticity of nanocrystalline diamonds

Abstract: This letter reveals that unusual elasticity of nanocrystalline diamond is consistently explained by stacking fault inside the diamond grains instead of the graphitic plate inclusion, which was only possible mechanism. Ab initio calculation shows that stacking fault introduced in the diamond structure behaves as graphitic sp2 bonds, and the elastic constants calculated from the strain-energy relationship agree with the acoustic measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…However, our results seem to be in general agreement with measurements of Tanei et al, 13,14 who found an increase of Poisson's ratio for decreasing grain size and an increasing sp 2 bonded carbon content.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, our results seem to be in general agreement with measurements of Tanei et al, 13,14 who found an increase of Poisson's ratio for decreasing grain size and an increasing sp 2 bonded carbon content.…”
Section: Resultssupporting
confidence: 93%
“…Brillouin light scattering measurements by Jiang et al 10 the gas phase of the hot filament CVD, while Poisson's ratio of nanocrystalline diamond was found to increase up to 0.18 after addition of 0.5% N 2 to the gas phase. 13,14 In a simple approach the Poisson's ratio can be measured by the change of the width of a beam during elongation. 15 This approach is relatively inaccurate; especially in the case where Poisson's ratio is small, such as for diamond.…”
mentioning
confidence: 99%
“…In principle, the deterioration of the stiffness is not surprising for an increase of the average interplane distance, while the Poisson ratio increases with an increase in the volume fraction of defects, but the simple model cannot reproduce these changes quantitatively. 60 Owing to the very large variety of possible morphologies and nanostructures, the relationship between microscopic structure and mechanical properties is still an open issue. This is true, especially, for NCD and UNCD diamond with strongly extended grain boundaries.…”
Section: E Nanocrystalline Diamondmentioning
confidence: 99%
“…Nanocrystalline diamond films grown under different growth conditions can exhibit similar average grain sizes but rather different elastic properties which also affect the thermal properties . Also the thermal conductivities of nanocrystalline diamond films show a wide range .…”
Section: Introductionmentioning
confidence: 99%